PENGARUH PARADIGMA MAZHAB FIKIH DALAM KAJIAN HADIS - Muslim, Adi Abdullah; Muna, Arif Chasanul (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This paper is about the historical process of the formation of fiqh Madhdhab, which was followed by the paradigm of thought that began to occur between Ahl al-Hadith and Ahl al-Fiqh, where both have their positions on the development of knowledge in the classical period. After the first century of Hijri during Umawiyyah rule, several Western history writers have stated in various literatures that they wrote, that Ahl al-Hadith appear to be in opposition to the government. The position of the government at that time is closer to the Islamic jurists who is a maker and controllers of laws in the government. Looking at the practice of law-making that happened at that time, how were the relations between Ahl al-Hadith and Ahl al-Fiqh according to some experts? There are dialogues and several theories resulting from the dialectics, accompanied by criticism of the groups who abuse their closeness to the government to falsify hadith for the benefit of their groups, due to their fanaticism. This research uses descriptive-analytical-critical nature, through a sociological-historical approach.